Exploring a pathway to carbon neutrality via reinforcing environmental performance through green process innovation, environmental orientation and green competitive advantage. (15th October 2021) - Zameer, Hashim; Wang, Ying; Vasbieva, Dinara G.; Abbas, Qaisar
Abstract: In the light of The Paris Agreement (COP 21), global leaders reached a consensus to curtail the increase in global temperature up to 2.0 °C ideally 1.5 °C pre-industrial level. Likewise, it has become a pathway to accomplish long-term goals of achieving carbon neutrality. In this regard, this paper aims to explore the role of green process innovation and environmental orientation toward environmental performance for achieving the long-term goal of carbon neutrality. In addition, this paper also discovers a mediating role of green competitive advantage in said context. Using data from a survey among managers of equipment manufacturing sector, the study employed structural equation modeling technique and found that green process innovation, environmental orientation and green competitive advantage significantly influence environmental performance. Subsequently, mediation analysis indicated that green competitive advantage partially mediates the relation from green process innovation and environmental orientation to environmental performance. In light of the carbon neutrality targets, the study highlight that improving environmental performance through green process innovation and environmental orientation can be a way-forward for manufacturing sector to play its role to achieve carbon neutrality. The study concludes with theoretical and practical implications. Highlights: This paper used data collected from managers. Partial mediation of green competitive advantage has been found. Green process innovation significantly improves environmental performance. Environmental orientation considerably reinforces environmental performance.